Hubungan Pola Menstruasi Dengan Kejadian Anemia Pada Remaja Putri Kelas VII SMPN 6 Kediri. - Yunarsih Yunarsih; Sumy Dwi Antono (coba, 2014)
Puberty is hormonal adolesence process which is signed with menstruation to girls adolesence. In early menstruation allowed menstrual cycle has not been regular,either excessive or menstrual cycle with longer interval. Excessively menstrual cycle causes the increase of iron substance need. So if iron substance has not been fulfilled it will be susceptible to happen anemia deficiency iron. The purpose of this research was to know whether there was a correlation between the menstrual cycle and anemia in 7 students of SMPN 6 kediri. Method which was used in the researchwas Survey Cross Sectional. Population in the research were all girls 7 th grade th gradestudentsof SMPN 6 Kediri who were taken suitable with inclusion criteria those were 80 students. Samples which were needed, were taken with Simple Random Sampling technique with number 45 samples. Data collecting was done by distributing questionnaire and cheking Hb. After data collected then tabulated, it was entered in Fisher Exact formula. It was gotten value p = 0.4 th >α = 0.1, it mean there wasno a correlation between the menstrual cycle and anemia in 7 grade students of SMPN 6 Kediri. Menstrual cycle is not the only reason for anemia. In this research 7 from 11 respondents who anemia, they have IMT belower. So, consume nutrition food can prevent anemia, although someone have excersive menstrual cycle. Keyword : Anemia, Menstrual Cycle, Adolescence